Investigation of low saline waterâs effects on relative permeability in carbonate reservoirs - Hematpour, H. (Penerbit UTM Press, 2016)
Low Salinity Water flooding (LSW) is one of the favorable subsets of water flooding EOR methods due to its great advantages over normal water flooding; having a low cost of operation and being environmentally-friendly. LSW has been studied in mathematical, experimentally and practically point of view in numerous numbers of sandstone cases in the worldwide. Existing of giant carbonate reservoirs containing a great amount of petroleum in the regions of the North Sea and the Middle East have been turned into a motivation for the relevant experts to focuses on the possibility of running an LSW project in a carbonate reservoir. Accordingly, this paper aims to investigate this possibility through running two sets of flooding tests on selected cores from one of Iranian carbonate reservoirs. In more details, on each core two water flooding tests have been conducted in which the first test have been run by a sample of water from the Persian Gulf with high salinity and in the second one the injected water has been from Karoon River with a lower rate of salinity. Then, the recovery factor from both tests of a target core has been compared. The results indicate that running an LSW have been caused improvement in recovery factors which was approved by relative permeability curves analysis. Â© 2016, Penerbit UTM Press. All rights reserved.